ENVIRONMENTAL PROBLEMS AND THEIR CONTROL MEASURES OF A GLASS FACTORY AT PESHAWAR (PAKISTAN) - Shah, Jehangir; Khan, A R; Rahman, Amin-ur-; Khan, Faridullah (Biological Sciences - PJSIR, 2004)
Detailed environmental survey/audit of a glass factory was carried out. Balanced sheets for raw materials and water con- sumption were prepared. Environmental problems especially associated with the unwise use of raw materials were identified and waste minimization techniques at source as well as at the end of pipe treatment were suggested. With the implementation of these techniques, the industry improved its production and achieved the national and international environmental quality standards.